The provincial governor : rights & duties under the 13th amendment - Marasinghe, M. L.; Gunatillake, Gehan; Jinadasa, Kamani (Colombo : Institute for Constitutional Studies, 2009)
With reference to Sri Lanka.
Includes index.
Keywords: Provincial governments -- Sri Lanka